THEORETICAL-METHODICAL ASPECTS OF THE APPROACHES ANDSTRATEGIES FOR SOCIAL WORK WITH INVOLUNTARY CLIENTS - CHILDRENFROM RESIDENTIAL CARE - Mitkova, Desislava (E-Journal VFU, 2024)
The concept of voluntary and involuntary clients is a central theme in social work. Social workers interact with clients on a daily basis who can be categorized into two broad groups: voluntary and involuntary. Differences in their personality, psychosocial and behavioral characteristics have a significant impact on the client-social worker relationship. Working with involuntary clients - children from residential care can be defined as particularly challenging. A good knowledge and understanding of the methods, strategies and approaches for working with 112 this specific contingent of clients in social work enables specialists to plan and implement an effective set of activities that best meet the needs and interests of children placed in residential social services.